GAMBARAN KUALITAS FISIK RUANG RAWAT INAP DI SALAH SATU RUMAH SAKIT DI BANJARNEGARA TAHUN 2025 - Awalinda Desiyanti; Joko Malis Sunarno; Bayu Suseno (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2025)
Hospitals as public service facilities, play a vital role in addressing various health issues; however, they also have the potential to become sources of nosocomial infections, which are infections acquired by patients during hospitalization. One of the preventive efforts to reduce nosocomial infections is by improving the physical quality of inpatient rooms to meet health standards. This study aims to describe the physical quality of inpatient rooms one of hospitals at Banjarnegara, focusing on parameters including temperature, humidity, noise level, lighting, and ventilation rate. This research is a descriptive study with a cross-sectional approach, utilizing measurement tools such as thermometers, hygrometers, sound level meters, lux meters, and anemometers. The population in this study includes all inpatient rooms, with a sample of 45 rooms selected through proportional random sampling. The study was conducted from April to June 2025, and the data were analyzed using univariate analysis. The results showed that most of the temperature (75.6%), humidity (77.8%), and ventilation rate (54.5%) measurements did not meet the standards, while the noise level (84.4%) and lighting (77.8%) were within acceptable limits. In conclusion, the physical quality of inpatient rooms has not fully complied with the Ministry of Health Regulation No. 2 of 2023, indicating the need for improvements to create an environment that supports the patient recovery process.